Answer: 7
Step-by-step explanation:
f(x) 3x+1
f(2) = 3(2) +1
f(2) = 6+1
= 7
In this equation w = -1.1
In order to find this, get all w values to the right side and all numbers to the left side.
-2.27 + 9.1w + 1.3w = -3.4w - 17.45 ----> combine like terms
-2.27 + 10.4w = -3.4w - 17.45 ----> add 3.4w to both sides
-2.27 + 13.8w = -17.45 ----> add 2.27 to both sides
13.8w = -15.18 -----> divide both sides by 13.8
w = -1.1
Answer:
48% is 12/25 as a fraction. So C
2x + y = 0
2x + 3 = 0
- 3 - 3
2x = -3
2 2
x = -1¹/₂
(x, y) = (-1¹/₂, 3)